The Effects of Mother-Plant Irrigation Schedule on the Quality Of Tomato (Lycopersicum esculentum) Seed - H Ibrahim; AS Gudugi; JA Oladiran; AJ Odofiin; MKA Adeboye; GO Oyetunde (Journal of Applied Sciences and Environmental Management)
A study was carried out to examine the quality of seeds of two tomato cultivars (‘Ibadan Local’ and ‘Ife 1’) produced under irrigation intervals of 2, 4, 6 and 8 days at the Federal University of Technology, Minna. Fruits were harvested when fully ripe and the seed/juice mixture (pulp) was removed immediately and left to ferment for four days after which the seeds were washed under running tap water and dried at room temperature. Seeds of the two cultivars were spread in open plastic Petri dishes and stored in a growth chamber at 30oC and about 70% relative humidity to accelerate ageing for 16 weeks. Seed samples were drawn and tested for germination, seedling emergence, seedling height and number of leaves per seedling, at 0, 2, 4, 6, 8, 10, 12, 14 and 16 weeks of storage. Results showed that seeds of “Ibadan Local” were significantly heavier than those of “Ife 1” but the trait was not significantly affected by irrigation interval. Seed viability declined as storage period increased irrespective of irrigation treatment in both cultivars. There was no consistent superiority of one irrigation interval over the other in respect of seed longevity over time. A general increase in seedling height and number of leaves per seedling was recorded as storage period progressed before a decline sets in at different ages. Generally, performance was best with seeds produced under 4 and 6 days irrigation intervals in both cultivars.